Conceptions of a group of teachers of early school years about basic astronomy concepts - Luiz Marcelo Darroz; Cleci Teresinha Werner da Rosa; Catieli Delazeri de Grandis (Universidad Distrital Francisco José de Caldas, 2016)
Astronomy is one of the most ancient sciences in the world and its development helped human beings to understand the universe around them, providing a wide list of knowledge in the field; however, it still seems to be restricted to a small group of individuals. Currently, considering the recommendation of the Brazilian National Curriculum Standards, Astronomy concepts became part of Science studies in the first years of elementary school. Therefore, the following question arises: are elementary school teachers trained and do they feel prepared to work with subjects related to Astronomy in the early years of elementary school? In an attempt to answer this question, a survey was applied to a group of teachers of early years of elementary school of the municipal system of Soledade, RS, Brazil. A questionnaire wasapplied including essay questions and multiple choice questions, as well as illustrations of astronomical phenomena, seeking to understand basic Astronomy concepts. The results obtained indicate that part of the teachers have an uncertain relationship with the subject, especially when addressing it in the school environment, and show, at the same time, to completely dominate some of the concepts in the field, while other teachers prove to be mistaken about certain topics.